KEBIJAKAN MINUMAN OLAHAN BERPEMANIS DALAM MEWUJUDKAN PERLINDUNGAN HAK ASASI MANUSIA TERHADAP KESEHATAN - Dina Aulia Insani; Erika Dewi Essary; Munawarah Pasaribu (Hang Tuah Law Journal, 2023)
Health is a fundamental human right, the highest standard not only curative and rehabilitative but also promotive and preventive. The production and consumption of sweetened beverages in Indonesia is increasing. This coincides with an increase in obesity. Obesity is a disease and is one of the risk factors for the incidence of non-communicable diseases, so prevention is necessary. Prevention and control of obesity through a human rights approach will clarify the obligations of the state and the community to raise awareness of the right to health. The purpose of this study is to analyze the policies on sweetened beverages related to human rights of health. The method of this study is normative legal research methods and an analytical approach using secondary data. The sweetened drinks policy is not only about the rules against manufacturers but pays more attention to the impact on health. Some countries have implemented policies through excise to limit sugar consumption. Prevention and control of obesity through a human rights approach will clarify the obligations of the state and the community to raise awareness of the right to health. Inter-ministerial policies, agencies, and national commissions are needed to issue integrated recommendations and guidelines so that the highest standards of health care can be achieved.